Pedigree reconstruction for triploid apple cultivars using single nucleotide polymorphism array data. Issue 1 (24th August 2022) - Howard, Nicholas P.; Micheletti, Diego; Luby, James J.; Durel, Charles‐Eric; Denancé, Caroline; Muranty, Hélène; Ordidge, Matthew; Albach, Dirk C.
Abstract : Societal Impact Statement: Many economically, culturally, and historically important apple cultivars are triploids, which have three copies of each chromosome instead of the more typical two copies in diploids. Despite their prevalence and importance, there have been conflicting reports regarding their origin and their ability to beget diploids. New genetic analysis methodologies outlined in this study have clarified the genetic origin of triploid apple cultivars and suggest that triploidy has been a dead end in historic apple pedigrees. The specific results of this study have resolved the pedigrees of many cultivars, including the famous English cultivar Cox's Orange Pippin and the oldest known US cultivar Roxbury Russet. Summary: In apple ( Malus  ×  domestica ), most cultivars are diploid, though a sizeable number are triploids, which tend to be stronger growing, more robust, and bear larger fruit. However, triploidy is also associated with strongly reduced fertility. Some recorded pedigrees for historical apple cultivars include triploids as parents of diploids, despite this reputation of poor fertility. This information, coupled with some initiatives using triploids in breeding efforts, result in confusion about how possible or common it is for triploids to be parents of diploid offspring. To date, no studies have systematically evaluated and identified pedigrees of triploid apple cultivars to resolve these contradictions. Here, we describe a method to make triploid genotype calls using Illumina Infinium single nucleotide polymorphism (SNP) array data through a novel Python script: ploidyClassifier. SNP data for 219 unique triploids was compared alongside 2498 unique diploid apple accessions to conduct pedigree reconstruction. Unreduced gamete‐donating parents were identified for over half of the triploid accessions. From those, reduced gamete‐donating parents were identified for nearly half. Full or partial pedigrees for many classic triploids were uncovered, including that of the oldest known American cultivar, 'Roxbury Russet'. All tested pedigrees from literature that listed triploids as parents of diploids were deemed false, including that of the well‐known 'Cox's Orange Pippin', whose previously unreported second parent was also identified here as 'Rosemary Russet'. These results together suggest that historic triploids are mostly or solely the product of diploid parentage and that triploidy has been a dead end in historic apple pedigrees. Abstract : Many economically, culturally, and historically important apple cultivars are triploids, which have three copies of each chromosome instead of the more typical two copies in diploids. Despite their prevalence and importance, there have been conflicting reports regarding their origin and their ability to beget diploids. New genetic analysis methodologies outlined in this study have clarified the genetic origin of triploid apple cultivars and suggest that triploidy has been a dead end in historic apple pedigrees. The specific results of this study have resolved the pedigrees of many cultivars, including the famous English cultivar Cox's Orange Pippin and the oldest known US cultivar Roxbury Russet.